Work motivation- a multivariate analysis among teachers of the Kerala Agricultural University - alexander George (Department of Agricultural Extension, College of Horticulture, 1996)
Work motivation, the inner urge that energises, directs and sustains work, was the dependent variable while the independent structure consisted of eighteen variables: Locus of control, achievement motive, power motive, affiliation motive, equity- sensitivity, growth need, relatedness need, existence need, preferred organizational culture, variety in job, identity of job, significance of job, autonomy in job, feedback through job, work climate, communication patterns, management style and morale. The sample of 150 teachers constituted 21.6 per cent of the total population of teachers in the Kerala Agricultural University. Distribution of teachers with respect to the variables mentioned above, relationships between the variables and determinants of work motivation were studied. Cadre-wise comparison of teachers was undertaken and teachers in teaching, research and extension institutions were also compared using ANOVA. All independent variables studied had strong correlations with work motivation. The relationship of affiliation motive preferred organizational culture and equity- sensitivity with work motivation was negative. Bunch-map analysis was used to confront the problem of multicollinearity and identify the determinants of work motivation: affiliation motive, existence need and identity of job. The study proposes a cohesive and unifying model to explain work motivation. Relevance of work motivation theories and practices with reference to the Indian socio-cultural context and applicability of existing models to educational and service sector organizations are discussed. Recommendations are made for the design and dynamics of human resource management practices applicable to the around 30,000 agricultural scientists in the country.